PENGARUH ENVIROMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Prayoga, Mhd Nanda; Asnahwati, Asnahwati (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on the firm value of mining sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019–2023 period. The independent variables consist of environmental disclosure, social disclosure, and governance disclosure, while the dependent variable is firm value, proxied by the Price to Book Value (PBV). This research employs a quantitative approach using multiple linear regression analysis. Secondary data were obtained from annual reports and sustainability reports of 10 mining companies selected through purposive sampling. The results show that partially, environmental disclosure has no significant effect on firm value, social disclosure has a positive but insignificant effect, while governance disclosure has a positive and significant effect on firm value. Simultaneously, the three ESG variables have a significant effect on firm value. These findings highlight the importance of good corporate governance practices as a key factor in enhancing investor confidence and firm value, while environmental and social disclosures need quality improvement to provide greater impact. This study is expected to serve as a reference for company management, investors, and academics in decision-making related to ESG implementation to enhance firm value.